Characterization of two genetically separable inorganic phosphate transport systems in Escherichia coli. - Willsky, G R (1980)
Inorganic phosphate (Pi) transport by wild-type cells of Escherichia coli grown in excess phosphate-containing media involves two genetically separable transport systems. Cells dependent upon the high affinity-low velocity Pst (phosphate specific transport) system have a Km of 0.43 +/- 0.2 microM Pi and a Vmax of 15.9 +/- 0.3 nmol of Pi (mg [dry weight]-1min-1) and will grow in the presence of arsenate in the medium. However, cells dependent upon the low affinity-high velocity Pit (Pi transport) system have a Km of 38.2 +/- 0.4 microM and a Vmax of 55 +/- 1.9 nmol of Pi (mg [dry weight]-1min-1), and these cells cannot grow in the presence of an arsenate-to-Pi ratio of 10 in the medium. Pi transport by both systems was sensitive to the energy uncoupler 2,4-dinitrophenol and the sulfhydryl reagent N-ethylmaleimide, whereas only the Pst system was very sensitive to sodium cyanide. Evidence is presented that Pi is transported as Pi or a very labile intermediate and that accumulated Pi does not exit through the Pst or Pit systems from glucose-grown cells. Kinetic analysis of Pi transport in the wild-type strain containing both the Pst and Pit transport systems revealed that each system was not operating at full capacity. In addition, Pi transport in the wild-type strain was completely sensitive to sodium cyanide (a characteristic of the Pst system).